Media Digital dalam Strategi Komunikasi Efektif Biro Skripsi untuk Mewujudkan Pelayanan Prima di Perguruan Tinggi - Rahmah Attaymini; Maya Sandra Rosita Dewi; Achmad Zuhri (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
Excellent service is a crucial aspect in the management of higher education institutions, particularly in academic services that directly interact with students, such as thesis administration units. To achieve excellent service, effective communication strategies are required so that students can obtain information easily, clearly, and transparently. Along with the rapid development of digital technology, cyber media has become a relevant communication tool that aligns with the current characteristics of students who are highly familiar with technology. This study aims to analyze effective communication strategies through the use of cyber media in supporting excellent service at the thesis administration office of the Faculty of Social Sciences and Humanities (FISHUM), UIN Sunan Kalijaga Yogyakarta. This research employs a descriptive qualitative method with data collected through Focus Group Discussions (FGDs) involving students and the thesis administration team. The findings reveal that the use of cyber media such as sosial media, WA and website is proven to be effective as a communication channel between the thesis administration team and students. Cyber media facilitates students in accessing information regarding the procedures and structure of thesis writing while reducing hesitation or reluctance to directly approach the administration staff. The discussion emphasizes that cyber-based communication strategies not only enhance openness and transparency of information but also minimize students’ reliance on traditional practices, such as depending on senior peers for information. Therefore, implementing effective communication through digital platforms is essential in realizing excellent service that is responsive, adaptive, and aligned with students’ needs in the digital era.